“Soy saludable”: modelo de investigación participativa para la promoción de comportamientos saludables (2014)
This article presents the results of study aimed at designing a model of advocacy strategies for healthy behaviors in the contemporary. It seeks to strengthen the autonomous decision -making processes for systemic and complexity, which enables a multidimensional approach, relational -oriented and integrated development of human potential behavior. The study assumed a methodological approach based on the Research Action Participation (RPA), investigative catalyst for thought, awareness method, transfer, application and attitude of strengthening decision making. This model was subjected to the validation phase by expert judges and the implementation of a pilot functional validation process with the participation of 6 study groups of young people in community contexts and university education. They found that young participants presented making process favorable decision against healthy behaviors, however evidence their vulnerability as a risk factor in healthy behaviors in social pressure environment. It is necessary to strengthen the development of assertive communication strategies and social coping supporting maintenance of consistent patterns in your lifestyle and in turn serve as input for a new culture of healthy social interaction.